Empowering parents for human immunodeficiency virus prevention: Health and sex education at home - Taygen Edwards; Ntombizodumo Mkwanazi; Joanie Mitchell; Ruth M. Bland; Tamsen J. Rochat (AOSIS, 2020)
Background: Improving health literacy amongst human immunodeficiency virus (HIV)-positive mothers could strengthen child and adolescent HIV prevention. The Amagugu intervention included health literacy materials to strengthen maternal communication and has demonstrated success in low-resource HIV-endemic settings. Objectives: Our aims were to (1) evaluate whether Amagugu materials improved health literacy leading to changes in parental behaviour towards communicating on topics such as HIV, health behaviours and sex education, and (2) explore what additional information and materials mothers would find helpful. Method: The Amagugu evaluation included 281 HIV-positive mothers and their HIV-uninfected children (6-10 years). Process evaluation data from exit interviews were analysed using content analysis and logistic regression techniques. Results: Of 281 mothers, 276 (98.0%) requested more educational storybooks: 99 (35.2%) on moral development/future aspirations, 92 (32.7%) on general health, safety and health promotion, and 67 (23.8%) on HIV and disease management. Compared to baseline, mothers reported that the materials increased discussion on the risks of bullying from friends (150; 53.4%), teacher problems (142; 50.5%), physical abuse (147; 52.3%) and sexual abuse (126; 44.8%). Most mothers used the 'HIV Body Map' for health (274; 97.5%) and sex education (267; 95.0%). The use of a low-cost doll was reported to enhance mother-child communication by increasing mother-child play (264; 94.3%) and maternal attentiveness to the child's feelings (262; 93.6%). Conclusion: Parent-led health education in the home seems feasible, acceptable and effective and should be capitalised on in HIV prevention strategies. Further testing in controlled studies is recommended.